Sex differences in absolute myocardial perfusion - Range, Felix T.; Kies, Peter; Schäfers, Klaus P.; Breithardt, Günter; Schober, Otmar; Wichter, Thomas; Schäfers, Michael A. (Nuklearmedizin - NuclearMedicine, 2016)
Aim: To investigate sex differences in myocardial perfusion especially in healthy individuals since former studies are rare and findings are controversial. Participants, methods: 26 subjects were enrolled: 16 healthy women (age: 34 ±7 years) were compared with 10 healthy men (age: 34 ± 3 years; p = ns). Myocardial blood flow (MBF) and coronary vascular resistance (CVR) were quantified at rest, during adenosine infusion and cold-pressor-testing, using positron emission tomography and radioactive-labelled water (H215O-PET). Results: Women showed higher MBF than men at rest (1.10 ± 0.18 vs. 0.85 ± 0.20 ml/min/ml; p = 0.003) and cold-stress (1.39 ± 0.38 vs. 1.06 ± 0.28 ml/min/ml; p = 0.026). Corrected for rate-pressure-product, baseline findings maintained significance (1.41 ± 0.33 vs. 1.16 ± 0.19 ml/min/ml; p = 0.024). CVR was lower in women at baseline (81 ± 14 vs. 107 ± 22 mmHg*ml-1*min*ml; p = 0.006) and during cold-pressor-testing (71 ± 17 vs. 91 ± 20 mmHg*ml-1*min*ml; p = 0.013). Under adenosine neither maximal MBF (4.06 ± 1.0 vs. 3.91 ± 0.88 ml/min/ml; p = ns) nor coronary flow reserve (3.07 ± 1.12 vs. 3.44 ± 0.92; p = ns) nor CVR (24 ± 8 vs. 24 ± 6 mmHg*ml-1*min*ml; p = ns) showed sex-related differences. Conclusion: Women show higher myocardial perfusion and lower coronary vascular resistance than men in physiologic states. Maximum perfusion and vasodilation under adenosine are not sex-specific.
Keywords: Sex differences; myocardial blood flow; adenosine-induced hyperaemia; endothelium-dependent flow reserve; positron emission tomography